Implementasi Sistem Informasi Pendidikan Madrasah Diniyah At-Taqwa Berbasis Website di Desa Tlogowulung Kec. Alian Kab.Kebumen - Ayu Putri Wahyuni; Endang Wahyuningsih (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
The advancement of information technology has become a crucial aspect of improving data management in educational institutions. Madrasah Diniyah At-Taqwa, located in Tlogowulung Village, Kebumen Regency, currently manages academic data manually, including student records, teacher data, class schedules, and student grades. This manual system often leads to data retrieval delays, limited accessibility, and a high risk of data loss. To address these issues, this research aims to design and implement a web-based educational information system tailored to the needs of Madrasah Diniyah At-Taqwa. The development process follows the Software Development Life Cycle (SDLC) using the Waterfall model, which includes phases such as requirements analysis, system design, implementation using the Laravel framework, black-box testing, and system maintenance. The system provides specific access and features for different user roles including Admins, teachers, and student guardians. Usability testing was conducted using the System Usability Scale (SUS), involving ten respondents. The average SUS score obtained was 77.75, which falls within the “Good to Excellent” usability range. This indicates that the system is easy to use, functionally appropriate, and well-received by users. Overall, the developed system effectively enhances data management processes, facilitates real-time access, and supports digital transformation in educational services